2020
DOI: 10.1093/europace/euaa179
|View full text |Cite|
|
Sign up to set email alerts
|

Left atrial fibrosis predicts left ventricular ejection fraction response after atrial fibrillation ablation in heart failure patients: the Fibrosis-HF Study

Abstract: Aims Atrial fibrillation (AF) and heart failure (HF) often coexist. Catheter ablation has been reported to restore left ventricular (LV) function but patients benefit differently. This study investigated the correlation between left atrial (LA) fibrosis extent and LV ejection fraction (LVEF) recovery after AF ablation. Methods and results In this study, 103 patients [64 years, 69% men, 79% persistent AF, LVEF 33% interquartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Previous studies have demonstrated that AF patients with LVSD could benefit from catheter ablation more than from medical treatment; a significant increase in LVEF after catheter ablation has been reported with a range between 8% and 20%. [9][10][11][12][13] In this study, an increase of LVEF at 12-month follow-up after catheter ablation was 21%, almost similar to, or even higher than the values in the previous studies. [8][9][10][11][12] The present study included patients with more severe systolic heart failure (LVEF ≤40%) than in previous studies (45% ≤ LVEF ≤50%).…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
See 3 more Smart Citations
“…Previous studies have demonstrated that AF patients with LVSD could benefit from catheter ablation more than from medical treatment; a significant increase in LVEF after catheter ablation has been reported with a range between 8% and 20%. [9][10][11][12][13] In this study, an increase of LVEF at 12-month follow-up after catheter ablation was 21%, almost similar to, or even higher than the values in the previous studies. [8][9][10][11][12] The present study included patients with more severe systolic heart failure (LVEF ≤40%) than in previous studies (45% ≤ LVEF ≤50%).…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
“…[9][10][11][12][13] In this study, an increase of LVEF at 12-month follow-up after catheter ablation was 21%, almost similar to, or even higher than the values in the previous studies. [8][9][10][11][12] The present study included patients with more severe systolic heart failure (LVEF ≤40%) than in previous studies (45% ≤ LVEF ≤50%). with LVSD were negatively correlated with improvement of LVEF after catheter ablation.…”
Section: Comparison With Previous Studiessupporting
confidence: 83%
See 2 more Smart Citations
“…After observing the left atrial geometry, pulmonary vein isolation (PVI) was performed under conscious sedation using intravenous fentanyl and via transseptal access to the left atrium. Assessment of LA surface area and LVA followed a clinical routine and were performed as described previously ( 15 , 16 ). A sequential high-density 3D bipolar voltage map (at least 300 points per patient) was constructed in all patients during sinus rhythm, guided by a 3D electroanatomic mapping system (CARTO3, Biosense Webster, or Ensite velocity, Abbott) using a circular mapping catheter (Lasso, 4 mm interelectrode spacing, Biosense Webster or Advisor FL, 3 mm, interelectrode spacing, Abbott).…”
Section: Methodsmentioning
confidence: 99%